Study of an Inorganic Ion Exchanger MgMn0.75Ti0.25O3 - Wang, Lintong; Jiang, Jinhe (Asian Journal of Chemistry, 2013)
The MgMn0.75Ti0.25O3 was synthesized by a solid state reaction crystallization method. using MgO, MnO2 and TiO2 as raw materials. The optimum conditions were obtained by thermal experiment, calcination temperature was at 900 ºC, calcination time was 4.5 h. The characterization results showed that the exchange capacity of Li+ was 8.9 mmol g-1 for Li+ in the solution.